New Players in the Interaction Between Beetle Polygalacturonases and Plant Polygalacturonase-Inhibiting Proteins: Insights From Proteomics and Gene Expression Analyses - Haeger, Wiebke; Wielsch, Natalie; Shin, Na Ra; Gebauer-Jung, Steffi; Pauchet, Yannick; Kirsch, Roy (Frontiers in Plant Science, 2021)
Plants possess various defense strategies to counter attacks from microorganisms or herbivores. For example, plants reduce the cell-wall-macerating activity of pathogen- or insect-derived polygalacturonases (PGs) by expressing PG-inhibiting proteins (PGIPs). PGs and PGIPs belong to multi-gene families believed to have been shaped by an evolutionary arms race. The mustard leaf beetle Phaedon cochleariae expresses both active PGs and catalytically inactive PG pseudoenzymes. Previous studies demonstrated that (i) PGIPs target beetle PGs and (ii) the role of PG pseudoenzymes remains elusive, despite having been linked to the pectin degradation pathway. For further insight into the interaction between plant PGIPs and beetle PG family members, we combined affinity purification with proteomics and gene expression analyses, and identified novel inhibitors of beetle PGs from Chinese cabbage (Brassica rapa ssp. pekinensis). A beetle PG pseudoenzyme was not targeted by PGIPs, but instead interacted with PGIP-like proteins. Phylogenetic analysis revealed that PGIP-like proteins clustered apart from “classical” PGIPs but together with proteins, which have been involved in developmental processes. Our results indicate that PGIP-like proteins represent not only interesting novel PG inhibitor candidates in addition to “classical” PGIPs, but also fascinating new players in the arms race between herbivorous beetles and plant defenses.